Mediating role of personality dysfunction and perceived stress on the relationship between stressful life events and psychological well-being among young adult women in India - Jereesh K. Elias; B. R. Sahithya; K. S. Paviyazhini (Discover Psychology)
Abstract Background Young adult women in India often face significant stress from navigating education, careers, and societal expectations, which can impact their psychological well-being. This study investigates how stressful life events (SLEs) affect psychological well-being and examines the mediating roles of personality dysfunction and perceived stress. Methods A cross-sectional survey was conducted with 190 Indian women aged 18–24. Participants completed measures of SLEs, psychological well-being, personality dysfunction, and perceived stress. Structural equation modeling was used to explore direct and indirect relationships. Results SLEs were linked to increased perceived stress and lower psychological well-being. Personality dysfunction was also associated with higher stress levels and reduced psychological well-being. Mediation analysis showed that both personality dysfunction and perceived stress significantly explained the pathway between SLEs and psychological well-being. Conclusions The findings highlight the intertwined roles of stress and personality in shaping young women’s mental health. These insights support targeted interventions to reduce the negative impact of stressful life events. Addressing personality functioning and incorporating stress management strategies at the university level may help enhance psychological well-being. Future research should consider the limitations of the current study design and sample characteristics, which may affect generalizability, and examine these relationships across more diverse populations using longitudinal designs to clarify causality.